AGAIN ON SUSTAINABLE DEVELOPMENT ￼FROM THE PERSPECTIVE OF ENVIRONMENTAL MEASUREMENTS - G. M. Abdurakhmanov; Sh. Sh. Gasanov; L. Sh. Akhmedova; R. T. Radzhabova (Юг России: экология, развитие, 2015)
Abstract. Aim. Research on the latest sustainable eco-development projects shows that the observed inconsistency of findings and recommendations is related to the underestimation of the socio-economic background of ecodevelopment. Illustrated system of equations allows us to calculate the ecological capacity and limits of human impacts on the entire hierarchy of territorial units from the rural areas to the biosphere as a whole. The purpose of the work is evaluating the basic model for sustainable eco-development at the regional level and ecological capacity as a basis for normalizing the anthropogenic burden within the country and its regions. Methods. Methods of measuring and evaluating the sustainability of geosystems.Location. The Republic of DagestanResults. Priority and highly effective measures are carried out to restore the functions of biological control over the environment.Main conclusion. In this paper we propose a way out of the current ecological crisis when fulfilling the given conditions for depopulation and restoring the stability of the living space on the basis of the fundamental mechanisms of biotic recovery of all environmental fluctuations.